Peningkatan Kualitas Pendidikan Anak Usia Dini Melalui Manajemen Administrasi - Khofifa Juliana Pilpres; Sulaika Marito Nst; Fadilah Ibrahim Nst; Miftahul Jannah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This research explores the positive impact of implementing administrative management in TK/PAUD-TPA-MDTA SYAWAL on improving the quality of early childhood education. This kindergarten/PAUD was founded by Mrs. Dra. Sunarti and led by Mrs. Ayu Sundari S.Pd, has experienced an interesting history since its inception. With six teachers and 60 students divided into three classes, this institution creates a dynamic and responsive learning environment. Through qualitative research methods, the results of this research reveal that careful administrative management at TK/PAUD-TPA-MDTA SYAWAL has a positive impact on resource availability, time management, parental involvement, and increasing the competence of teaching staff. These findings provide important insights for other PAUD institutions in improving the effectiveness of administrative management and the quality of early childhood education